Identification, characterization and structure of a new Delta class glutathione transferase isoenzyme - Rungrutai Udomsinprasert (2018)
The insect GST (glutathione transferase) supergene family encodes a varied group of proteins belonging to at least six individual classes. Interest in insect GSTs has focused on their role in conferring insecticide resistance. Previously from the mosquito malaria vector Anopheles dirus, two genes encoding five Delta class GSTs have been characterized for structural as well as enzyme activities. We have obtained a new Delta class GST gene and isoenzyme from A. dirus, which we name adGSTD5-5. The adGSTD5-5 isoenzyme was identified and was only detectably expressed in A. dirus adult females. A putative promoter analysis suggests that this GST has an involvement in oogenesis. The enzyme displayed little activity for classical GST substrates, although it possessed the greatest activity for DDT [1,1,1-trichloro-2,2-bis-(p-chlorophenyl)ethane] observed for Delta GSTs. However, GST activity was inhibited or enhanced in the presence of various fatty acids, suggesting that the enzyme may be modulated by fatty acids. We obtained a crystal structure for adGSTD5-5 and compared it with other Delta GSTs, which showed that adGSTD5-5 possesses an elongated and more polar active-site topology. © 2005 Biochemical Society.